The Impact of Corporate Welfare Policies on Job Satisfaction of Garment Workers - Trần Thị Cẩm Tú; Lê Thị Hồng Nhung; Đổ Hoàng Trâm (Journal of Technical Education Science, 2026)
This study investigates the effects of corporate welfare policies on job satisfaction among garment industry workers in Vietnam. A quantitative research design was employed, utilizing survey data collected from 240 garment workers at manufacturing enterprises. Exploratory factor analysis, reliability testing, and multiple regression were employed for data analysis. The results indicate that salary and allowances, health insurance and medical care, and working conditions have significant positive impacts on job satisfaction. Conversely, work–life balance policies were found to negatively affect satisfaction. Other welfare factors, including social welfare, training and career development, and recognition and rewards, do not exhibit statistically significant effects. The regression model explains over 80% of the variance in job satisfaction, highlighting the critical role of economic benefits and social security-related welfare in a labor-intensive, low-income context. The findings suggest that improving financial compensation, health-related benefits, and workplace conditions is essential for enhancing job satisfaction and retention among garment workers.